MODEL PERMAINAN TRADISIONAL MASYARAKAT ISLAM MELAYU SUMATERA SELATAN DALAM MEREDUKSI KECENDRUNGAN ANAK BERMAIN “SKIP CHALLENGGE" - Neni Noviza; Arinil Hidayah Bt Mohd Kassim (Wardah, 2018)
The purpose of this study is to identify traditional games in the Malay Muslim community of South Sumatra, to identify the values found in traditional games and to find the traditional game model of Malay Muslim community in South Sumatra in reducing the tendency of children to play Skip Challenge. The method used in this research is qualitative verification method. Subjects in this study are students and lecturers in Faculty of Dakwah and Communication. Data collection techniques using observation techniques, interviews, documentation and triangulation. Data analysis technique using Miles and Huberman model is Data Reduction, Data Dispute and Conclusion (Verification). From the result of the research, there are 17 kinds of traditional game of Malay Muslim community in South Sumatera, namely: gudang kero, gamang, adang-adangan, cak engleng, ekar, epat cadang, tukupan pedekan biji para/asem, yeye/tali, dakocan/uwong-uwongan, gambaran/ambulan, bentengbentengan, karet gelang, cetoran, ore’an, pantak lele dan layangan. The values of character education contained in the game the value of honesty, the value of sportsmanship, the value of cooperation, the value of strategy settings and leadership value. The values in Islam contained in the game are: Leadership Soul (Imamah), Cooperation (Ta'awun), Relieved (Wus'ah), Enforcing justice ('adalah) Obedient Rule (Ta'at), Honest (Amanah) Work hard (Sa'iy), Not Arrogant, (Tawadhu '), Clever (Fatanah), Motivator (Istibaqah) and Gender Equality (Musawah). Keywords : Traditional Games, Skip Challennge